TEACHERS’ STRATEGIES FOR EVALUATING READING FLUENCY IN SECOND GRADE OF ELEMENTARY SCHOOL - Wildatun Nisa, Tasya; Boeriswati, Endry; Puryanto, Edi (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the strategies employed by teachers to evaluate reading fluency in second grade elementary school students. Utilizing a qualitative descriptive approach, data were collected through interviews with experienced second grade teachers and a review of relevant literature. The results reveal that teachers implement a variety of strategies and media, including picture books, reading cards, storytelling, and educational games, to both engage students and assess their reading fluency effectively. These approaches not only facilitate accurate evaluation but also foster students’ motivation and interest in reading. The findings highlight the importance of integrating traditional and modern assessment tools that are tailored to the developmental needs of young learners. This research provides valuable insights for educators seeking to enhance their methods for evaluating reading fluency in elementary education.